Psychoanalysis and ethics: the necessity of perspective - Black, David M. (The new library of psychoanalysis, 2024)
"Psychoanalysis and Ethics: The Necessity of Perspective is an attempt to look deeply into the relationship between psychoanalysis and ethics, and in particular into the failure of traditional psychoanalytic thinking to recognise the foundational character of ethical values. In recent years, partly because of the climate crisis, the need for an "ethical turn" in our thinking has been recognised with increasing urgency. Using different historical lenses, and with special reference to the thought of the philosopher Emmanuel Levinas and pioneering American psychoanalysts such as Hans Loewald and Stephen Mitchell, the author discusses the perspectives needed in addition to those of science if the facts of "psychic reality" are to be more adequately recognised. In particular, this book emphasises the importance of a coherent account of the role of ethics in the development both of the individual and of society. Psychoanalysis and Ethics is essential reading for those concerned for the importance of ethics in psychoanalytic practice and theory, and more widely for those seeking to understand the place of ethics and religion in psychological development"--